Effects of in Utero Exposure to Di(n-butyl) Phthalate for Estrogen Receptors α, β, and Androgen Receptor of Leydig Cell on Rats. (July 2014) - Wakui, Shin; Shirai, Masaru; Motohashi, Masaya; Mutou, Tomoko; Oyama, Noriko; Wempe, Michael F.; Takahashi, Hiroyuki; Inomata, Tomoo; Ikegami, Masahiro; Endou, Hitoshi; Asari, Masao
Estrogens and androgens affect male and female reproductive systems. Recently, we reported that prenatal di( n -butyl) phthalate (DBP) exposure induced atypical Leydig cells (LCs) hyperplasia during adulthood. The present study investigated the expression of estrogen receptor α (ERα), estrogen receptor β (ERβ), and androgen receptor (AR) in LCs of 5-, 7-, 9-, 14-, and 17-week-old Sprague-Dawley (srl) rats whose dams had been administered DBP intragastrically at 100 mg/kg/day or the vehicle (corn oil) from days 12 to 21 postconception. Immunohistochemical, Western blotting, and reverse transcription polymerase chain reaction analyses revealed that the expressions of ERα, ERβ, and AR proteins and mRNAs in the DBP group were similar to those of the vehicle group at 5 and 7 weeks, but significantly higher ERα and lower ERβ and AR levels were observed in the DBP group at 9 to 17 weeks. The rats prenatally exposed to DBP had seminiferous tubule degeneration and atypical hyperplasia of LCs during adulthood, which was associated with an increase in expression of ERα and a decrease of ERβ and AR in the testis.